2010
DOI: 10.1177/159101991001600112
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral Agenesis of the Internal Carotid Artery Associated with Basilar Artery Aneurysm Treated via the Endovascular Route

Abstract: Bilateral agenesis of the internal carotid artery is a rare anomaly of embryonic development frequently associated with intracranial aneurysm. We describe a case involving an aneurysm that burst in the third middle of the basilar artery and exhibited a bilateral agenesis of the internal carotid artery. The aneurysm was treated via an endovascular route using detachable coils.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…ACOM is the most frequent site of aneurysm formation in agenesis of the ICA [2] . Aneurysms were also located in the PCOM, MCA, basilar artery, or basilar tip in this anomaly [9 , 10 , 12] . However, aneurysm at the SCA's origin associated with the unilateral ICA's agenesis has not been reported before in the literature.…”
Section: Discussionmentioning
confidence: 71%
“…ACOM is the most frequent site of aneurysm formation in agenesis of the ICA [2] . Aneurysms were also located in the PCOM, MCA, basilar artery, or basilar tip in this anomaly [9 , 10 , 12] . However, aneurysm at the SCA's origin associated with the unilateral ICA's agenesis has not been reported before in the literature.…”
Section: Discussionmentioning
confidence: 71%
“…Type B cases involve the ipsilateral ACA and MCA, with the supply of blood through the ACoA. Type C cases show bilateral agenesis of the ICA, with the supply to the anterior circulation through carotid-vertebrobasilar anastomoses; a review of the literature found that this is generally accomplished through hypertrophy of the PCoA, 9 , 14) and the present case is thought to correspond to type C. Type D cases show unilateral agenesis of the cervical portions of the ICA with an intercavernous communication to the ipsilateral carotid siphon from the contralateral cavernous ICA. In type E, small ACAs are supplied by bilateral hypoplastic ICAs, while the MCAs are supplied by enlarged PCoAs.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, our patient was offered microsurgical management, which she declined. Of the seven reported cases of bilateral carotid hypoplasia, only one underwent successful clipping of the aneurysm [ 18 ], whereas six refused treatment when informed about the risks of intervention.…”
Section: Discussionmentioning
confidence: 99%